Placental pathology - Eguren Velasquez, Leopoldo (2015)
We have presented, as a preliminary communication, the results of the histopathological study of 120 previously selected placentas and two cases of chorioepithelioma found in screening tests that are routinely performed in all uterine contents obtained by curettage "Post abortum" in the pavilion No. 9 of the Maternity of Lima.